Prevalence and Factors Associated with Musculoskeletal Disorders among Thai Burley Tobacco Farmers - Amarin Kongtawelert (2022)
This cross-sectional analysis study aimed to identify the prevalence and factors associated with musculoskeletal disorders (MSDs) among Thai Burley tobacco farmers. Subjects included 603 burley tobacco farmers from Sukhothai province. Farmers were interviewed twice, (during planting and harvesting seasons), with a questionnaire consisting of demographic and health char-acteristics, musculoskeletal symptoms, and ergonomic exposure questions. The subjects average age was 49.5 years, more were female (58.5%), most had only a primary education (74.3%), 38% were overweight or obese. Farmers had a significantly higher prevalence of MSDs in the lower back (37.1%), knee (28.7%), shoulder (22.9%), wrist (19.9%), and hip (8.3%) during the harvesting season than in the planting season (p < 0.05). Models found that factors influencing MSDs prevalence during planting included long work hours in seedling, tasks such as topping tobacco plants, and using machine tools, after controlling for age, gender, and body mass index (BMI). While in the harvesting season, models found tasks conducted as a group had lower MSDs prevalence than individual work when carrying fresh tobacco to the barn, piercing/threading and curing the leaves, baling the bundles, and transporting the finished goods. We recommended working in groups to reduce workload and MSDs, especially during harvesting, in burley tobacco farming.